Surfactant Protein D Recognizes Multiple Fungal Ligands: A Key Step to Initiate and Intensify the Anti-fungal Host Defense - Madan, Taruna; Kishore, Uday (Frontiers in Cellular and Infection Microbiology, 2020)
With limited therapeutic options and associated severe adverse effects, fungal infections are a serious threat to human health. Innate immune response mediated by pattern recognition proteins is integral to host defense against fungi. A soluble pattern recognition protein, Surfactant protein D (SP-D), plays an important role in immune surveillance to detect and eliminate human pathogens. SP-D exerts its immunomodulatory activity via direct interaction with several receptors on the epithelial cells lining the mucosal tracts, as well as on innate and adaptive immune cells. Being a C-type lectin, SP-D shows calcium- and sugar-dependent interactions with several glycosylated ligands present on fungal cell walls. The interactome includes cell wall polysaccharides such as 1,3-β-D-glucan, 1,6-β-D-glucan, Galactosaminogalactan Galactomannan, Glucuronoxylomannan, Mannoprotein 1, and glycosylated proteins such as gp45, gp55, major surface glycoprotein complex (gpA). Recently, binding of a recombinant fragment of human SP-D to melanin on the dormant conidia of Aspergillus fumigatus was demonstrated that was not inhibited by sugars, suggesting a likely protein-protein interaction. Interactions of the ligands on the fungal spores with the oligomeric forms of full-length SP-D resulted in formation of spore-aggregates, increased uptake by phagocytes and rapid clearance besides a direct fungicidal effect against C. albicans. Exogenous administration of SP-D showed significant therapeutic potential in murine models of allergic and invasive mycoses. Altered susceptibility of SP-D gene-deficient mice to various fungal infections emphasized relevance of SP-D as an important sentinel of anti-fungal immunity. Levels of SP-D in the serum or lung lavage were significantly altered in the murine models and patients of fungal infections and allergies. Here, we review the cell wall ligands of clinically relevant fungal pathogens and allergens that are recognized by SP-D and their impact on the host defense. Elucidation of the molecular interactions between innate immune humoral such as SP-D and fungal pathogens would facilitate the development of novel therapeutic interventions.